Exploring the lived experience of performance-related health and wellbeing among flautists - Wang, Jiayi; Welch, Graham F. (Frontiers in Psychology, 2024)
The study has investigated the lived experience of flautists, focusing on their experiences and perceptions of performance-related physical discomfort, injury and related mental health challenges that they might have encountered in practice and performance. The aims of the research have been to provide flautists with an opportunity to reflect on any physical or psychological performance issues in their own words, and to understand the subjective meaning of these experiences.A basic qualitative approach was used for gathering data. All the fieldwork was undertaken during or immediately after the Covid-19 pandemic. Consequently, the participating flautists were deliberately selected using professional networks on the basis of their answers to a pre-interview initial questionnaire related to the characteristics of their personal backgrounds and their experiences, as well as being able to participate remotely.There have been two data collection phases. Phase 1 was a specially designed pre-interview questionnaire drawing on themes from appropriate literature. Phase 2 built on the pre-interview questionnaire responses and was designed as semi-structured interviews, undertaken on Zoom, and included a 'River of Flute-playing Experience' activity during the interview. The 'River of Experience' method is an autobiographical research tool in which participants were asked to annotate key biographical experiences and challenges at various points along their drawing of a meandering river. The combined data analyses drew on thematic analysis.The eight participants reported a personal history of performance-related health and wellbeing challenges that they had faced at some point in their lives. The findings reveal that flautists encounter health-related challenges associated with their practice and performances, and the data suggest that they each require an understanding of likely performance-related health challenges and supportive resources to assist them in managing these challenges. The participants' diverse experiences highlight the importance of managing health and the value of supportive social connections. They cope with health challenges by integrating passion, resilience, and adaptability into their lives, finding ways to grow and continue to thrive in their flute-playing journey. The study underscores the need for comprehensive health education and support resources for flautists, emphasising the significance of resilience and adaptability in fostering health, wellbeing, and success.